Kedudukan Royalti Hak Cipta Lagu sebagai Objek Gugatan dalam Perceraian - Abdul Rahman, Aisyah N; Mahmudah, Masrifatun; Muharuddin (Universitas Muhammadiyah Yogyakarta, 2025)
Dispute over the distribution of copyright royalties as joint property in divorce cases in the Religious Court, as reflected in the Decision of the West Jakarta Religious Court Number 1662/Pdt.G/2023/PA.JB. Copyright royalties are a legal issue because they have a dual character, namely as personal rights as well as economic rights that can be enjoyed together in a marriage. This study aims to analyze the legal status of copyright royalties in marriage and examine their resolution through religious court mechanisms. The research method used is normative juridical with a statutory approach and case studies, using primary data from court decisions and secondary data from intellectual property law literature and Islamic family law, which are analyzed qualitatively. The results of the study show that royalties generated during marriage are classified as joint property that can be divided during divorce, although moral rights to the creation remain the personal property of the creator, and the distribution of royalties must consider the principles of justice and economic protection of both parties, so that royalties in divorce are not only viewed as individual rights, but also as marital assets that are subject to the principle of division of joint assets